2018
DOI: 10.1101/371971
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oxytocin modulates the intrinsic dynamics between attention-related large scale networks

Abstract: Attention and salience processing have been linked to the intrinsic between-and within-network dynamics of large scale networks engaged in internal (default mode network, DN) and external attention allocation (dorsal attention, DAN, salience network, SN). The central oxytocin (OXT) system appears ideally organized to modulate widely distributed neural systems and to regulate the switch between internal attention and salient stimuli in the environment. The current randomized placebo (PLC) controlled between-sub… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 117 publications
1
11
0
Order By: Relevance
“…Determining the co‐activation and intrinsic connectivity networks of the identified region in the left anterior insula cortex revealed that it represents a core node of a bilateral network encompassing anterior insular and adjacent ventrolateral prefrontal regions as well as anterior cingulate and midcingulate regions. This network clearly resembles the rs‐fMRI “salience” network, anchored in the anterior insula and the midcingulate cortex (Seeley et al, 2007), which plays an important role in the regulation of interoceptive versus external guided attention (Xin et al, 2021; Yao et al, 2018) and the guidance of flexible behavior (Menon & Uddin, 2010; Seeley et al, 2007). Abnormalities in this network have been repeatedly observed in chronic pain (Cauda et al, 2009; Hemington, Wu, Kucyi, Inman, & Davis, 2016; Wu, Inman, & Davis, 2013) and neuropsychiatric conditions, including depression (Manoliu et al, 2014; Shao et al, 2018), anxiety (Geng, Li, Chen, Li, & Gu, 2016), or addiction (Klugah‐Brown et al, 2020, 2021) which are commonly found to be co‐morbid in chronic pain (Bair, Robinson, Katon, & Kroenke, 2003; Finan & Smith, 2013).…”
Section: Discussionmentioning
confidence: 85%
“…Determining the co‐activation and intrinsic connectivity networks of the identified region in the left anterior insula cortex revealed that it represents a core node of a bilateral network encompassing anterior insular and adjacent ventrolateral prefrontal regions as well as anterior cingulate and midcingulate regions. This network clearly resembles the rs‐fMRI “salience” network, anchored in the anterior insula and the midcingulate cortex (Seeley et al, 2007), which plays an important role in the regulation of interoceptive versus external guided attention (Xin et al, 2021; Yao et al, 2018) and the guidance of flexible behavior (Menon & Uddin, 2010; Seeley et al, 2007). Abnormalities in this network have been repeatedly observed in chronic pain (Cauda et al, 2009; Hemington, Wu, Kucyi, Inman, & Davis, 2016; Wu, Inman, & Davis, 2013) and neuropsychiatric conditions, including depression (Manoliu et al, 2014; Shao et al, 2018), anxiety (Geng, Li, Chen, Li, & Gu, 2016), or addiction (Klugah‐Brown et al, 2020, 2021) which are commonly found to be co‐morbid in chronic pain (Bair, Robinson, Katon, & Kroenke, 2003; Finan & Smith, 2013).…”
Section: Discussionmentioning
confidence: 85%
“…The cognitive processes of distancing reappraisal during the anticipation period mainly involves attentional control, whereas the stimulus presentation period additionally involves self-projection, affective self-reflection, and cognitive control (Koenigsberg et al, 2010;Ochsner et al, 2012;Powers and LaBar, 2019). Combined with findings from our prior resting state study (Xin et al, 2018), it may be hypothesized that OXT may modulating pre-stimulus attentional control of threatening social information. With respect to behavior performance during emotion regulation, no effects of OXT per se were observed, although the high anxiety group exhibited a marginal significant improvement of reappraisal success following OXT, suggesting that OXT may have the potential to improve cognitive emotion regulation in high anxiety individuals.…”
Section: Oxytocin Differentially Modulated Amygdala Responses In Highmentioning
confidence: 81%
“…However, without prior knowledge, the unsupervised nature might lead to challenges in explaining the detected communities and clarifying their links with brain function and behavior. Other approaches where prior knowledge can be combined with the independent component analysis have been adopted to detect brain networks [5,59], resulting from a more robust detection of brain networks. Incorporating prior knowledge in community detection thus is one of the future directions in brain network science.…”
Section: Clustering Of Dynamical Coupling Patternsmentioning
confidence: 99%